(untitled) (Global Journal of Management and Business Research, 2021)
Research on entrepreneurship has focused on traditional business models based on activities with a well-localized geographic existence We have placed our problem in the field of digital entrepreneurship by studying the factors that have an impact on the creation and the success of e-businesses This study focuses on the individual factors the strategic factors and the factors of quality of service which motivate net entrepreneurs and contribute to the success of cyber businesses in Tunisia